2011
DOI: 10.1108/02640471111177053
|View full text |Cite
|
Sign up to set email alerts
|

Web citation persistence over time: a retrospective study

Abstract: PurposeBy studying a large number of citations in the LIS field, this paper seeks to examine carefully the persistence status of web resources specified by their domains and type of files.Design/methodology/approachAll 2005‐2008 volumes of six LIS journals ranked by ISI Thomson Reuters were selected. From 1,181 papers, 37,791 citations were recorded. Only original articles, which had a list of references, were included in the study. The persistence of web citations was checked by directly following the cited U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…With social media building inroads into our lives and impacting knowledge accessibility, it was found that this did not have a major role to play in the professional arena of researchers as the open access journals were not completely trusted due to concerns regarding predatory open access journals (Watkinson et al, 2015). However, Riahinia et al (2011) findings suggest that there is a persistence of web citation (Bhat and Kumar, 2008;Maharana et al, 2006). According to them, "the means per articles of web and print citations are 4.09, and 27.9, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With social media building inroads into our lives and impacting knowledge accessibility, it was found that this did not have a major role to play in the professional arena of researchers as the open access journals were not completely trusted due to concerns regarding predatory open access journals (Watkinson et al, 2015). However, Riahinia et al (2011) findings suggest that there is a persistence of web citation (Bhat and Kumar, 2008;Maharana et al, 2006). According to them, "the means per articles of web and print citations are 4.09, and 27.9, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This yielded a ratio of 3.64 web citations per dissertation. Riahinia et al (2011) considered six LIS journals during 2005-2008 for their study. Of the 37,791 citations, 4,840 (12.8%) were web citations.…”
Section: Ajim 742mentioning
confidence: 99%
“…She found that URLs at .gov top-level domain are more vulnerable to link rot than those at the .org top-level domain. Riahinia et al (2011) analyzed 37,791 citations extracted from six LIS scholarly journals, of which 4,840 (12.8 percent) were web citations. The mean averages of web and print citations per article were 4.09 and 27.9 respectively.…”
Section: Previous Workmentioning
confidence: 99%
“…Print-to-web citations and web-to-print citations are now fairly common and thus it seems inevitable that web resources are becoming favored in scholars' communication. The cited content is considered as available if it can be found either at the URLs included in the sample citation or elsewhere on the web (Riahinia et al 2011). During the last decade many journal articles, including refereed articles, contain citations to web sources.…”
Section: Introductionmentioning
confidence: 99%